Neuropsychological and phonological evaluation in the Apert's syndrome: study of two cases - Ciasca,Sylvia Maria (2001)
This study evaluated two cases of Apert's syndrome, through phonological, cognitive, and neuropsychological instruments and correlated the results to complementary exams. In short, this study reveals the necessity of application of neuropsychological, cognitive and phonological evaluation and correlation of the results with complementary testings because significant differences can be present in the Apert's syndrome.